2015
DOI: 10.3109/13561820.2014.1002907
|View full text |Cite
|
Sign up to set email alerts
|

Legislating interprofessional collaboration: A policy analysis of health professions regulatory legislation in Ontario, Canada

Abstract: Changes to Ontario's health professions regulatory system were initiated through various legislative amendments. These amendments introduced a legislative obligation for health regulatory colleges to support interprofessional collaboration (IPC), collaborate where they share controlled acts, and incorporate IPC into their quality assurance programs. The purpose of this policy analysis was to identify activities, strategies, and collaborations taking place within health professions regulatory colleges pertainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Literature regarding rehabilitation service delivery in schools has largely focused on collaboration between rehabilitation professionals and educators to promote student outcomes (Borg & Drange, 2019;Wintle, Krupa, Cramm, & DeLuca, 2017). Our findings regarding collaboration are consistent with existing literature in: (a) reinforcing the importance of collaboration, (b) reporting on essential features of collaborative relationships, (c) acknowledging the need for coordination among complex interfacing systems, and, (d) acknowledging that collaboration is situated within existing global, governmental, and professional discourses (Archibald, 2017;Flynn & Power-defur, 2013;Regan, Orchard, Khalili, Brunton, & Leslie, 2015;Villeneuve & Shulha, 2012;World Health Organization, 2010). However, despite broad acceptance of the importance of collaboration, research specific to interprofessional collaboration in schools indicates a lack of knowledge about how interprofessional collaboration meets the needs of educators and students, and how it includes students' families (Kennedy et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Literature regarding rehabilitation service delivery in schools has largely focused on collaboration between rehabilitation professionals and educators to promote student outcomes (Borg & Drange, 2019;Wintle, Krupa, Cramm, & DeLuca, 2017). Our findings regarding collaboration are consistent with existing literature in: (a) reinforcing the importance of collaboration, (b) reporting on essential features of collaborative relationships, (c) acknowledging the need for coordination among complex interfacing systems, and, (d) acknowledging that collaboration is situated within existing global, governmental, and professional discourses (Archibald, 2017;Flynn & Power-defur, 2013;Regan, Orchard, Khalili, Brunton, & Leslie, 2015;Villeneuve & Shulha, 2012;World Health Organization, 2010). However, despite broad acceptance of the importance of collaboration, research specific to interprofessional collaboration in schools indicates a lack of knowledge about how interprofessional collaboration meets the needs of educators and students, and how it includes students' families (Kennedy et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…When system-level actions are essential to increase the recognition of the roles of healthcare professionals and legitimize IPC [ 46 ], they must be complemented by organizational and inter-individual level changes to favor professionals’ acceptance and embracement. For example, a policy analysis conducted in Ontario (Canada) [ 63 ] reported that a legislative support favoring IPC did not suppress important barriers. Moreover, since the implementation of IPC through a top-down approach increased professionals’ impression of an injunction to collaborate, several reviews underlined the importance of using bottom-up strategies to tailor IPC to its context and favor its acceptance by professionals [ 11 31 37 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are actually three forms of umbrella laws: the first two are top-down, with legislators giving mandates. The two models both use the descriptive scope of practice approach: the first is specific to the health and social care professions, as in Ontario, Canada [49], or Australia [35], and the second is global for all professions regardless of the activity sector, as in Quebec, Canada [44]. The latter form is bottom up: the umbrella law has the objective of fostering cooperation or collaboration among colleges, with individual statutes for every regulated profession, as in Nova Scotia, Canada [39,50].…”
Section: Macro-levelmentioning
confidence: 99%